Efektivitas Peran Pesantren Mahasiswa dalam Pencegahan Pergaulan Bebas - Moza Apriliano; Triono Ali Mustofa; Mutoharrun Jinan (Pusat Riset dan Inovasi Nasional, 2025)
The problem of promiscuity at this time is increasingly making people nervous in developed and developing countries, people are starting to worry about this problem, especially people who live in big cities. Currently, promiscuity is included in many cases that have been found and have exceeded the limit, especially in the realm of students who live outside the city and live in boarding houses, so a breakthrough is needed to deal with this case, namely the presence of Student Boarding Schools in the midst of student life. The role of the Student Boarding School in preventing promiscuity is very important to do, because the presence of this student boarding school aims to provide a positive environment and sufficient provision of religious and social knowledge. The purpose of this study is to understand and describe the effectiveness of the role of student pesantren in preventing promiscuity in Pesma and Shabran hut. The method used in this research is field research. This research was conducted at Pesantren Mahasiswa KH Mas Mansur and Hajjah Nuriyyah Shabran UMS. The results obtained from this study are the role of student pesantren in preventing promiscuity, namely the role of forming discipline, providing a good environment, shaping student productivity and others, differences and similarities in approaches in preventing promiscuity in Pesma and Shabran huts, namely firmness and flexibility in rules, and the impact on student morale when students live in Pesma and Shabran huts.